(untitled) (Patrimônio e Memória, 2022)
This paper shows the history of the company town of Fabricación Española de Fibras Artificiales (FEFASA) in Miranda de Ebro (Burgos, Spain). Built between 1951 and 1958, it consisted of 326 detached houses with a large plot, as well as the necessary facilities (church, schools for boys and girls, social building and sports fields). In the 1970s, the houses were sold to their tenants and the equipments transferred to public and private institutions. Based on the field work carried out, it can be affirmed that, despite the almost 70 years that have elapsed since its construction, the neighborhood mostly preserves the original appearance of its houses or, at least, with few alterations, which gives it an extraordinary heritage value as an example of the employer promotion of working-class housing during the first Francoism.